Regionale Arbeitsmärkte in der 'Großen Rezession': Dynamik regionaler Arbeitslosenquoten in Deutschland, Frankreich und Großbritannien im Krisenjahr 2009 - Christian Reiner (University of Salzburg, Department of Social Sciences and Economics, 2010)
– Regional labour markets in the 'Great Recession': The evolution of regional unemployment rates in Germany, France and the United Kingdom in 2009. Contrary to the already encompassing literature on the differentiated effects of the 'Great Recession' on states, the article takes a regional economic perspective. The stated research question is 'Which factors might explain the spatially unequal development of unemployment rates at the regional level?'. Using a cross-section data-set with the percentage point increase of regional unemployment rates between 2008 and 2009 as the dependent variable and a set of regional and national variables as independent variables, a multiple linear regression model is estimated. After detecting spatial autocorrelation for the OLS-estimators, the model is re-estimated and a spatial error model with ML-estimators is computed. It turns out that the share of low-skilled has a significant positive effect on the change of regional unemployment rates. Furthermore, the financial centres showed a significant better resilience than other regional economies. Because of the strong influence of the national variables in these models, separate models are estimated for France and UK. It is shown that the same variables have quite different effects. This questions the existence of a common explanation for regional unemployment dynamics in Europe.
Keywords: J64; R11; R23; 330; Regionale Arbeitsmärkte; Große Rezession; Arbeitslosigkeit; Räumliche Ökonometrie